Serum Vitamin B12 as a Risk Factor and Prognostic Indicator in Acute Ischemic Stroke: A Case-Control Study at a Tertiary Care Hospital Mirpurkhas (Sindh): Serum Vitamin B12 as a Risk Factor and Prognostic Indicator in Acute Ischemic Stroke - Ahsan, Naveed; Shahbaz, Lal; Asim, Shazia; Erum, Humaira; Ansari, Masud Ali; Javaid, Amber (Pakistan Journal of Health Sciences, 2025)
Ischemic stroke is among the main causes of disability and death globally. Vitamin B12, through its role in homocysteine metabolism, may help prevent stroke, as its deficiency increases stroke risk. Objective: To compare the serum level of vitamin B12 in stroke patients and controls. Methods: The current case-control study was conducted in Mirpurkhas, Sindh, included 75 patients who suffered from stroke and 75 control subjects. Serum level of vitamin B12 and the levels of homocysteine were evaluated, along with the severity of stroke and functional outcomes were evaluated using the National Institutes of Health Stroke Scale (NIHSS) and Modified Rankin Scale (mRS), respectively, at discharge and 28 days. Statistical analysis explored associations with the severity of the stroke and its outcomes. Results: Stroke patients showed significantly lower levels of vitamin B12 (188.4 ± 43.6 pg/mL) than controls (352.7 ± 54.1 pg/mL, p<0.001). Vitamin B12 insufficiency (<200 pg/mL) was more prevalent in stroke patients (65.3%) compared to controls (18.7%, p<0.001). NIHSS scores were higher in deficient patients (13.1 ± 4.2) than those with insufficient (9.6 ± 3.1) or sufficient levels (7.5 ± 2.5, p<0.001). Worse functional outcomes (mRS 3.9 ± 1.2) were noted in deficient patients compared to insufficient (2.8 ± 0.8, p=0.007) and sufficient levels (2.3 ± 0.6, p<0.001). Logistic regression identified vitamin B12 deficiency as an independent stroke risk factor (OR=5.9, 95% CI: 2.9–12.3, p<0.001). Conclusions: It was concluded Vitamin B12 deficiency was associated with increased stroke severity and poorer outcomes, suggesting its potential role in stroke management.